Addressing Colorectal Cancer Disparities in Unhoused Populations: A Call for Equitable Access and Compassionate Care - Decker, Hannah; Erickson, Caroline; Wick, Elizabeth (Clinics in colon and rectal surgery, 2025)
Housing is essential for health. Unhoused individuals have markedly worse health status than the general population culminating in higher rates of premature mortality. Cancer is a leading cause of death in older unhoused adults. Caring for unhoused patients at risk for or with colorectal cancer poses challenges at every stage of oncologic care: prevention, screening, diagnosis, treatment, and follow-up. These challenges result in later stages at diagnosis and worse overall survival. Health systems can work to advance health equity in colorectal cancer in unhoused patients by improving access to care, transitions of care, health care quality, and focusing on socioeconomic/environmental impact.